PERANAN ASETOSAL SEBAGAI ANTI-TROMBOTIK TERHADAP METABOLISME TROMBOKSAN A2 (TXA2) DAN PROSTASIKLIN PGI2) - Astuti, Pudji (STOMATOGNATIC- Jurnal Kedokteran Gigi, 2010)
Low dose aspirin can be used to reduce transient ischemic attack and unstable t angina. Besides, it may also be used as thrombosis prophylaxis in artery coronary (heart artery). Working mechanism ofacetosal is inhibit cyclo-oxygenase enzyme leading to the inhibitation of thromboxane A2 and prostacyclin formation, whereas they have contrary function. Thromboxane A2 stimulate formationof platelet aggregation while prostacyclin inhibit plateletÂ  ggregation. How acetosal plays the role on thromboxane A2 and prostacyclin metabolism, affecting the prolonged bleeding time.